El carácter desinteresado de la apreciación de lo bello en la estética kantiana - Cerna, Jorge (2014)
The present paper has the purpose of analyzing the notion of disinterest in Kant’s aesthetics. The first part focuses on Shaftesbury’s and Schopenhauer’s aesthetic approaches, wherein the presence of disinterest in relation to the appraisal of beauty is highlighted –albeit, as will be seen, in very different senses than the one proposed by Kant. The second part approaches the Analytics of beauty, around which some reflections about disinterest will be attempted in order to pay attention to disinterest as proposed by Kant, not only as a negative element, but also with an open, positive, connotation that enables a relationship with the world different than usual.